Cold city outdoor space utilisation patterns and constraints: a systematic review of empirical evidence - Caili, Li; Maruthaveeran, Sreetheran; Shahidan, Mohd Fairuz; Caiwen, Li (Elsevier, 2024)
Urban outdoor spaces, as significant venues for outdoor activities, are closely linked to urban residents' quality of life and physical health. However, evidence suggests that prolonged and cold winters in cold cities, characterised by low temperatures, ice and snow, and frigid winds, profoundly impact residents' engagement in outdoor activities. Understanding the patterns of residents' utilisation of outdoor spaces and the constraints they face in the cold urban environment is crucial. Despite this, there is currently a lack of systematic reviews synthesizing evidence. This study conducts a systematic literature review from the social ecology perspective, organizing relevant evidence on residents' usage patterns, constraints, and preferences for outdoor spaces in cold urban environments. The literature review spans studies published from 2000 to 2023, drawing data from six electronic databases, including Google Scholar, Web of Science, and Scopus. Ultimately, 31 articles (N = 31) were included in the review. The findings indicate that outdoor spaces in cold urban areas are influenced by a range of factors, encompassing individual, social, physical, and perceptual environmental attributes. Consequently, a conceptual framework based on social ecology is developed to comprehend the usage and constraints of outdoor spaces in cold urban environments. This research provides valuable insights for urban planners and designers in designing and planning outdoor spaces in cold cities.